Determination of neonicotinoid insecticide residues in sugarcane juice using LCMSMS. (15th February 2018) - Suganthi, A.; Bhuvaneswari, K.; Ramya, M.
Highlights: Development of a modified QuEChERS procedure for five neonicotinoid pesticides. Suitable performance characteristics (sensitivity and recovery) were obtained with sugarcane juice matrix. Chromatographic separation and quantification by Liquid Chromatography. Qualitative identification of products by tandem Quadruple Mass detector. Abstract: A simple, sensitive and inexpensive LC–MS/MS method was developed and validated for for the simultaneous detection and quantification of (five) neonicotinoid insecticides in sugarcane juice. The juice samples were extracted with acetonitrile and subsequent cleanup was done by dispersive solid-phase extraction (QuEChERS method). The quantification was carried out by liquid chromatography–tandem mass spectrometry with electrospray ionization source (LC-ESI-MS/MS). After the optimization of the extraction parameters, the method was validated by evaluating linearity, limits of detection and quantification, precision (repeatability) and accuracy (recovery). Validation was based on analyses at three fortification levels that showed satisfactory recoveries (62.06–129.93%) and high precision (RSDs between 2.52% and 14.57%). Detection levels for all the five analytes ranged from 0.0007 to 0.002 μg g −1 and quantification level ranged from 0.002 to 0.005 μg g −1, respectively.